UV photocuring hydrophobic material for bathroom and preparation method thereof
By introducing thiol and vinyl groups into organozirconium nanoparticles, silicone resins and silicone materials, UV light excitation click reactions, UV light cured hydrophobic materials were prepared, solving the problem of existing bathroom materials being treated at high temperatures, and achieving efficient and environmentally friendly hydrophobic effects.
Patent Information
- Application Number
- CN202411749894.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
AI Technical Summary
Existing bathroom materials are prone to water and oil stains during use, which is difficult to clean. The existing hydrophobic technology has problems such as unsuitable high-temperature treatment conditions, high energy consumption and poor hydrophobic effect. It is urgently needed to have a green and environmentally friendly and efficient preparation method.
By introducing photocurable thiol and vinyl groups into organozirconium nanoparticles, silicone resins and silicone materials, UV light-curing hydrophobic materials are prepared by using ultraviolet light to excite the click reaction, and rapid photocuring at room temperature.
It realizes rapid photocuring of bathroom hydrophobic materials at room temperature, has excellent hydrophobic and anti-fouling properties, good adhesion and high hardness, and is suitable for use in bathroom materials, solving the problem of traditional materials being treated at high temperatures and reducing energy consumption.
Smart Images

Figure BDA0005164747310000041 
Figure BDA0005164747310000071 
Figure BDA0005164747310000081
Abstract
Description
Technical Field
[0001] The invention belongs to the field of sanitary materials, and in particular relates to a photocurable hydrophobic material and a preparation method thereof. Technical Background
[0002] With the continuous growth of my country's economic strength and the improvement of people's living standards, consumers have raised their demands for bathroom products from appearance design, structure and function to artistry, intelligence, simplicity, energy saving, functionality, etc. Bathroom products such as faucets, pendants, showers, floor drains, etc. are frequently exposed to water, oil smoke, dust, etc. during use, and are prone to water stains and oil stains that are difficult to clean. Over time, they seriously affect their appearance and service life, which is also a major user pain point that needs to be solved urgently.
[0003] At present, bathroom materials, such as ceramic tiles, are waterproofed mainly by hydrophobic siloxanes that are hydrolyzed at high temperatures to form a hydrophobic coating, but the hydrophobic effect is not good enough. At the same time, high-temperature treatment conditions are not suitable for some heat-sensitive bathroom materials. In addition, high-temperature heating consumes a lot of energy, which does not meet the requirements of energy conservation and environmental protection. It is urgent to use a green and environmentally friendly technology to efficiently prepare hydrophobic materials for bathrooms. Photocuring technology is an efficient, environmentally friendly, energy-saving, and high-quality surface treatment technology, and is known as a new technology for green industry in the 21st century. Moreover, it is photocured at room temperature, and there is no requirement for the heat resistance of the material, so it is an ideal preparation method for bathroom materials.
[0004] Patent CN115448596B invented a zirconia-based bathroom ceramic and its preparation method, zirconia @ MoS2 core-shell particles, kaolin, potassium feldspar, sodium feldspar, nano titanium dioxide, dolomite, zinc oxide, aluminum oxide, hafnium nitride, metal powder ball milling and mixing evenly, and then mixed with organic silicon polymer, organic polyzirconium precursor, POSS sol, ethylene glycol, water to obtain glaze, the glaze is applied to the surface of the body by high pressure glaze spraying process, and fired, the firing temperature is 1180-1250℃, the firing time is 50-90min. Traditional bathroom products in the bathroom are mainly made of ceramics, marble and other materials, which have the disadvantages of high production cost, cumbersome process, complex process, low yield, etc. Bathroom products made of polymer materials can solve the above problems very well, so bathtubs and wash basins made of polymer materials have been widely used. Patent CN112430372A invented a polymer material for bathroom. The invention adopts polymer resin, aggregate as the polymer material skeleton, and filler as filler, so that the polymer material has strong support performance and improves the physical properties of the polymer material. The overall material of this method is composed of polymer materials. Through testing, it is found that its wear resistance is improved compared with commercially available bathroom materials. The only drawback is that injection molding also requires high temperature conditions and high energy consumption, which is not suitable for heat-sensitive polymer materials. Summary of the invention
[0005] In order to overcome the shortcomings and deficiencies of the above-mentioned prior art, the primary purpose of the present invention is to provide a method for preparing a UV light-curable hydrophobic material for bathrooms. The UV light-curable hydrophobic material for bathrooms achieves the purpose of photocuring by introducing photocurable thiol and vinyl groups into organic zirconium nanoparticles, silicone resins and silicone materials: the thiol and vinyl groups undergo a click reaction under the irradiation of ultraviolet light, and are rapidly photocured at room temperature. At the same time, the oxygen inhibition problem commonly existing in the photocuring process is overcome, and the photocuring can be performed in the air, which has a wider range of applications.
[0006] Another object of the present invention is to provide a method for preparing the above-mentioned organic zirconium nanoparticles, organic silicon resin and organic silicon material.
[0007] Another object of the present invention is to provide an application of UV light-cured hydrophobic materials. The introduction of organic zirconium nanoparticles improves the hardness of the material, the introduction of organic silicon resin improves the adhesion of the material, and the introduction of organic silicon material improves the hydrophobic and antifouling properties of the material. The prepared light-cured material has extremely high hardness, good adhesion and excellent hydrophobic and antifouling properties, and is particularly suitable for use as a bathroom material.
[0008] The purpose of the present invention is achieved through the following solutions:
[0009] A method for preparing a UV light-curable hydrophobic material for bathroom use comprises the following steps: firstly, alkyl zirconium alcohol, mercaptosilane and long-chain alkyl silane are subjected to hydrolysis and condensation to prepare organic zirconium nanoparticles modified with mercapto groups and long-chain alkyl groups; secondly, alkyl silane and mercaptosilane are subjected to hydrolysis and condensation to prepare organic silicone resin; and octamethylcyclotetrasiloxane (D4) and 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane (D4) are subjected to hydrolysis and condensation to prepare organic silicon resin. C=C ), 1,3-divinyltetramethyldisiloxane (vinyl double-capped) for condensation reaction to prepare end-side vinyl polysiloxane organosilicon material. Then, the prepared organozirconium nanoparticles, organosilicon resin and organosilicon material are uniformly mixed with a small amount of solvent and then photocured under UV light.
[0010] Preferably, the mercapto- and long-chain alkyl-modified organic zirconium nanoparticles are prepared by the following method: alkyl zirconium alcohol, mercaptosilane, long-chain alkyl silane, catalyst and solvent are uniformly mixed, the temperature is increased for hydrolysis and condensation, and after a period of reaction, the solvent is removed by rotary evaporation to obtain mercapto- and long-chain alkyl-modified organic zirconium nanoparticles.
[0011] Preferably, the organic silicone resin is prepared by the following method: alkyl silane, mercapto silane, a catalyst and a solvent are uniformly mixed, the temperature is increased for hydrolysis and condensation, and after a period of reaction, the solvent is removed by rotary evaporation to obtain the organic silicone resin.
[0012] Preferably, the organosilicon material of the terminal vinyl polysiloxane is prepared by the following method: D4, D4 C=C After the vinyl double-capped end and the catalyst are evenly mixed, the temperature is raised to carry out a condensation reaction. After a period of reaction, the system is neutralized with an alkali until it becomes neutral, thereby obtaining a terminal vinyl polysiloxane.
[0013] The zirconium alkyl alcohol is one of zirconium ethoxide, zirconium n-propoxide, zirconium n-butoxide or zirconium tert-butoxide.
[0014] The mercaptosilane is one of (3-mercaptopropyl)trimethoxysilane and (3-mercaptopropyl)triethoxysilane.
[0015] The long-chain alkyl silane is at least one of dodecyltrimethoxysilane, hexadecyltrimethoxysilane, octadecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltriethoxysilane and octadecyltriethoxysilane.
[0016] The catalyst is at least one of acetic acid and dilute hydrochloric acid.
[0017] The solvent is at least one of ethanol and isopropanol.
[0018] The heating for hydrolysis condensation means raising the temperature to 40-60° C. for reaction for 4-8 hours; preferably, raising the temperature to 50° C. for reaction for 6 hours.
[0019] The amounts of the alkyl zirconium alcohol, mercaptosilane, long-chain alkyl silane, catalyst and solvent meet the following requirements: the molar ratio of the alkyl zirconium alcohol, mercaptosilane and long-chain alkyl silane is 1:0.4-0.6:0.4-0.6, the amount of the catalyst is 1%-5% of the total mass of the alkyl zirconium alcohol, mercaptosilane and long-chain alkyl silane, and the amount of the solvent is 100%-300% of the total mass of the alkyl zirconium alcohol, mercaptosilane and long-chain alkyl silane.
[0020] The alkylsilane is one of 1,2-bis(trimethoxysilyl)ethane and 1,6-bis(trimethoxysilyl)hexane.
[0021] The mercaptosilane is one of (3-mercaptopropyl)trimethoxysilane and (3-mercaptopropyl)triethoxysilane.
[0022] The catalyst is at least one of acetic acid and dilute hydrochloric acid.
[0023] The solvent is at least one of ethanol and isopropanol.
[0024] The heating for hydrolysis condensation means raising the temperature to 40-60° C. for reaction for 4-8 hours; preferably, raising the temperature to 50° C. for reaction for 6 hours.
[0025] The amounts of the alkylsilane, mercaptosilane, catalyst and solvent are such that the molar ratio of the alkylsilane to the mercaptosilane is 1:0.4-0.6. The amount of the catalyst is 1%-5% of the total mass of the alkylsilane and the mercaptosilane, and the amount of the solvent is 100%-300% of the total mass of the alkylsilane and the mercaptosilane.
[0026] The catalyst is at least one of sulfuric acid and trifluoromethanesulfonic acid.
[0027] The condensation reaction is carried out at 40-80° C. for 8-12 hours, preferably at 60° C. for 10 hours.
[0028] The catalyst meets the following requirements: the amount of catalyst is D4, D4 C=C and 1% to 5% of the total mass of the vinyl double head.
[0029] The alkali is at least one of sodium carbonate and sodium bicarbonate.
[0030] A UV light-curing hydrophobic material for bathroom use prepared by the method.
[0031] Preferably, the structural formula of the UV light-curable hydrophobic material for bathroom use is specifically as follows:
[0032]
[0033] Wherein R1 is a long-chain alkyl group, R2 is a mercapto group, R3 is an alkyl group, R4 is a mercapto group, m=20-40, and n=20-40.
[0034] The above-mentioned UV light-curing hydrophobic material for bathroom is dissolved by adding a small amount of solvent in a certain proportion, and then adding a small amount of photoinitiator and stirring evenly, and then applied to the bathroom surface such as metal, glass, ceramic or plastic. After a short period of UV light exposure (such as 5s) in the air, it can be completely dry on the surface. The light-cured material has good hydrophobicity, heat resistance and transparency, as well as good adhesion, high hardness and good wear resistance, and is widely used in bathroom materials.
[0035] The certain proportion refers to that the organic zirconium nanoparticles, the organic silicon resin and the organic silicon material are added in a substance amount ratio of 1:1:1.7 to 2.3.
[0036] The photoinitiator refers to a compound that can generate free radicals under ultraviolet light irradiation, and is at least one of 2-hydroxy-2-methylpropiophenone (Darocur1173), 1-hydroxy-cyclohexyl benzophenone (Darocur184), 2,4,6-trimethylbenzoyl-ethoxy-phenylphosphine oxide (TEPO) and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO); the added amount of the photoinitiator is 1% to 4% of the total mass of the organic zirconium nanoparticles, the organic silicon resin and the organic silicon material.
[0037] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0038] The hydrophobic material for sanitary ware prepared by the present invention has a simple preparation method, and introduces mercapto groups and double bonds capable of photocuring into organic zirconium nanoparticles, organic silicon resin and organic silicon materials at the same time, and can be UV-cured at room temperature and in the air, and is not afraid of oxygen inhibition, and is very convenient to use. In addition, the curing speed is fast, the cross-linking degree is high, and the UV-cured material has excellent hydrophobicity, heat resistance, transparency, adhesion and hardness, and is widely used in the field of sanitary ware. DETAILED DESCRIPTION
[0039] The present invention is further described in detail below in conjunction with the examples, but the embodiments of the present invention are not limited thereto. The raw materials or instruments involved in the present invention can be purchased directly from the market. For process parameters not particularly noted, conventional techniques can be used.
[0040] Unless otherwise specified, the reagents used in the examples can be purchased from the market.
[0041] Example 1
[0042] Zirconium n-propoxide, (3-mercaptopropyl)trimethoxysilane, dodecyltrimethoxysilane in a molar ratio of 1:0.5:0.5 and ethanol solvent are added to a reaction container, stirred evenly, and a small amount of catalyst acetic acid is added dropwise, the temperature is raised to 50°C for hydrolysis condensation reaction, the reaction is carried out for 6 hours, and the solvent is removed by rotary evaporation to obtain organic zirconium nanoparticles modified with mercapto groups and long-chain alkyl groups.
[0043] 1,2-bis(trimethoxysilyl)ethane and (3-mercaptopropyl)trimethoxysilane in a molar ratio of 1:0.5 and ethanol solvent are added to a reaction container, stirred evenly, and a small amount of catalyst acetic acid is added dropwise, the temperature is raised to 50°C for hydrolysis condensation reaction, the reaction is carried out for 6 hours, and the solvent is removed by rotary evaporation to obtain a silicone resin.
[0044] Place D4, D4 C=C The mass ratio of the two is 1:1, 5% vinyl double head is used as a capping agent, 2% sulfuric acid is used as a catalyst, and after being evenly mixed, the temperature is raised to 60°C for condensation reaction. The reaction is stopped after 10 hours of reaction, and the system is cooled to room temperature and neutralized with sodium bicarbonate until the system is neutral, which is the silicone material of terminal vinyl polysiloxane.
[0045] The prepared organic zirconium nanoparticles, organic silicon resin and organic silicon material were mixed evenly with ethyl acetate, and 1% of photoinitiator 1173 and TPO were added. The mixture was coated with a wire rod to form a film, and a photocured hydrophobic material was obtained after irradiation with ultraviolet light for 5 seconds.
[0046] Example 2
[0047] Zirconium n-butoxide, (3-mercaptopropyl)triethoxysilane, dodecyltriethoxysilane in a molar ratio of 1:0.5:0.5 and ethanol solvent are added to a reaction container, stirred evenly, a small amount of catalyst acetic acid is added dropwise, the temperature is raised to 50°C for hydrolysis condensation reaction, the reaction is carried out for 6 hours, and the solvent is removed by rotary evaporation to obtain organic zirconium nanoparticles modified with mercapto groups and long-chain alkyl groups.
[0048] The preparation of the organosilicon material containing organosilicon resin and terminal vinyl polysiloxane is as in Example 1.
[0049] The prepared organic zirconium nanoparticles, organic silicon resin and organic silicon material were mixed evenly with ethyl acetate, and 1% of photoinitiator 1173 and TPO were added. The mixture was coated with a wire rod to form a film, and a photocured hydrophobic material was obtained after irradiation with ultraviolet light for 5 seconds.
[0050] Example 3
[0051] The preparation of organic zirconium nanoparticles modified with mercapto groups and long-chain alkyl groups is as in Example 1.
[0052] 1,6-bis(trimethoxysilyl)hexane, (3-mercaptopropyl)trimethoxysilane in a molar ratio of 1:0.5 and ethanol solvent are added to a reaction container, stirred evenly, a small amount of catalyst acetic acid is added dropwise, the temperature is raised to 50°C for hydrolysis condensation reaction, the reaction is carried out for 6 hours, and the solvent is removed by rotary evaporation to obtain a silicone resin.
[0053] The preparation of the organosilicon material containing vinyl polysiloxane at the end is as in Example 1.
[0054] The prepared organic zirconium nanoparticles, organic silicon resin and organic silicon material were mixed evenly with ethyl acetate, and 1% of photoinitiator 1173 and TPO were added. The mixture was coated with a wire rod to form a film, and a photocured hydrophobic material was obtained after irradiation with ultraviolet light for 5 seconds.
[0055] Example 4
[0056] The preparation of organic zirconium nanoparticles modified with mercapto groups and long-chain alkyl groups is as in Example 1.
[0057] 1,2-bis(trimethoxysilyl)ethane, (3-mercaptopropyl)triethoxysilane in a molar ratio of 1:0.5 and ethanol solvent are added to a reaction container, stirred evenly, a small amount of catalyst acetic acid is added dropwise, the temperature is raised to 50°C for hydrolysis condensation reaction, the reaction is carried out for 6 hours, and the solvent is removed by rotary evaporation to obtain a silicone resin.
[0058] The preparation of the organosilicon material containing vinyl polysiloxane at the end is as in Example 1.
[0059] The prepared organic zirconium nanoparticles, organic silicon resin and organic silicon material were mixed evenly with ethyl acetate, and 1% of photoinitiator 1173 and TPO were added. The mixture was coated with a wire rod to form a film, and a photocured hydrophobic material was obtained after irradiation with ultraviolet light for 5 seconds.
[0060] Example 5
[0061] The preparation of organic zirconium nanoparticles modified with mercapto groups and long-chain alkyl groups is as in Example 1.
[0062] 1,6-bis(trimethoxysilyl)hexane, (3-mercaptopropyl)triethoxysilane in a molar ratio of 1:0.5 and ethanol solvent are added to a reaction container, stirred evenly, a small amount of catalyst acetic acid is added dropwise, the temperature is raised to 50°C for hydrolysis condensation reaction, the reaction is carried out for 6 hours, and the solvent is removed by rotary evaporation to obtain a silicone resin.
[0063] The preparation of the organosilicon material containing vinyl polysiloxane at the end is as in Example 1.
[0064] The prepared organic zirconium nanoparticles, organic silicon resin and organic silicon material were mixed evenly with ethyl acetate, and 1% of photoinitiator 1173 and TPO were added. The mixture was coated with a wire rod to form a film, and a photocured hydrophobic material was obtained after irradiation with ultraviolet light for 5 seconds.
[0065] Example 6
[0066] The preparation of organic zirconium nanoparticles and organic silicone resin modified by mercapto groups and long-chain alkyl groups is as in Example 1.
[0067] Place D4, D4 C=C The mass ratio of the two is 1:1, 2.5% of vinyl double head is used as a capping agent, 2% of sulfuric acid is used as a catalyst, and after being evenly mixed, the temperature is raised to 60°C for condensation reaction. The reaction is stopped after 10 hours of reaction, and the system is cooled to room temperature and neutralized with sodium bicarbonate until the system is neutral, which is the silicone material of terminal vinyl polysiloxane.
[0068] The prepared organic zirconium nanoparticles, organic silicon resin and organic silicon material were mixed evenly with ethyl acetate, and 1% of photoinitiator 1173 and TPO were added. The mixture was coated with a wire rod to form a film, and a photocured hydrophobic material was obtained after irradiation with ultraviolet light for 5 seconds.
[0069] The properties of the UV-cured hydrophobic materials in the above examples are shown in the following table.
[0070] Table 1. UV curable hydrophobic material properties of the examples
[0071]
[0072]
[0073] in:
[0074] UV curing time refers to the irradiation time of a 2 kW high pressure mercury lamp commonly used in the market. The radiation energy in 5 seconds is 300 mj / cm 2 ;
[0075] The hydrophobic angle is the contact angle measured by a commercially available contact angle meter using water as the liquid. A hydrophobic angle greater than 90° indicates good hydrophobicity.
[0076] Heat resistance is the data obtained by measuring the weight loss relationship of the cured film using Mettler's thermal analyzer (Mettler TGA / DSC). The test conditions are nitrogen atmosphere, heating from 30°C to 800°C, and the heating rate is 10°C / min. Here T 5% Indicates the temperature at which the cured film loses 5% of its weight, T max Indicates the temperature at which the weight loss rate of the cured film is the maximum;
[0077] Transparency is the transmittance of a cured film with a thickness of 20 microns measured by ultraviolet spectroscopy. The test instrument is Shimadzu's UV-2600, and the test wavelength is 400-800nm (visible light wavelength range);
[0078] The adhesion test is based on the cross-cut method of GB / T 9286-2021, with 0 being the best and 5 being the worst;
[0079] The hardness test is based on the pencil hardness method of GB / T 6739-2022, with 9B being the softest and 9H being the hardest.
[0080] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a UV light-curing hydrophobic material for bathroom use, characterized in that The following steps are involved: The UV light-curable hydrophobic material is obtained by introducing photocurable mercapto groups and vinyl groups into organic zirconium nanoparticles, organic silicon resins and organic silicon materials.
2. The method for preparing a UV light-curing hydrophobic material for bathroom use according to claim 1, characterized in that The specific steps include: Firstly, alkyl zirconium alcohol, mercaptosilane and long-chain alkyl silane are hydrolyzed and condensed to prepare mercapto- and long-chain alkyl-modified organic zirconium nanoparticles; secondly, alkyl silane and mercaptosilane are hydrolyzed and condensed to prepare silicone resin; finally, octamethylcyclotetrasiloxane, 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane and 1,3-divinyltetramethyldisiloxane are condensed to prepare silicone material with terminal vinyl polysiloxane; then, the prepared organic zirconium nanoparticles, silicone resin and silicone material are uniformly mixed with a small amount of solvent and then photocured under UV light.
3. The method for preparing a UV light-curing hydrophobic material for bathroom use according to claim 2, characterized in that: The organic zirconium nanoparticles modified with mercapto groups and long-chain alkyl groups are prepared by the following method: alkyl zirconium alcohol, mercaptosilane, long-chain alkylsilane, catalyst and solvent are uniformly mixed, and then heated for hydrolysis and condensation. After a period of reaction, the solvent is removed by rotary evaporation to obtain organic zirconium nanoparticles modified with mercapto groups and long-chain alkyl groups; The organic silicone resin is specifically prepared by the following method: after uniformly mixing alkyl silane, mercapto silane, a catalyst and a solvent, heating to carry out hydrolysis and condensation, after a period of reaction, rotary evaporation to remove the solvent to obtain the organic silicone resin; The organosilicon material of the end-side vinyl polysiloxane is specifically prepared by the following method: octamethylcyclotetrasiloxane, 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane and vinyl double-capped catalyst are uniformly mixed, the temperature is increased to carry out condensation reaction, and after a period of reaction, the end-side vinyl polysiloxane is obtained by neutralizing with alkali until the system is neutral.
4. The method for preparing a UV light-curing hydrophobic material for bathroom use according to claim 3, characterized in that: The zirconium alkyl alcohol is zirconium ethanol, zirconium n-propoxide, zirconium n-butoxide or zirconium tert-butoxide; The mercaptosilane is trimethoxysilane or triethoxysilane; The long-chain alkyl silane is at least one of dodecyltrimethoxysilane, hexadecyltrimethoxysilane, octadecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltriethoxysilane and octadecyltriethoxysilane; The catalyst is at least one of acetic acid and dilute hydrochloric acid; The solvent is at least one of ethanol and isopropanol; Heating for hydrolysis condensation means raising the temperature to 40-60°C for 4-8 hours; The amounts of the alkyl zirconium alcohol, mercaptosilane, long-chain alkyl silane, catalyst and solvent meet the following requirements: the molar ratio of the alkyl zirconium alcohol, mercaptosilane and long-chain alkyl silane is 1:0.4-0.6:0.4-0.6, the amount of the catalyst is 1%-5% of the total mass of the alkyl zirconium alcohol, mercaptosilane and long-chain alkyl silane, and the amount of the solvent is 100%-300% of the total mass of the alkyl zirconium alcohol, mercaptosilane and long-chain alkyl silane.
5. The method for preparing a UV light-curing hydrophobic material for bathroom use according to claim 3, characterized in that: The alkylsilane is one of 1,2-bis-ethane and 1,6-bis-hexane; The mercaptosilane is trimethoxysilane or triethoxysilane; The catalyst is at least one of acetic acid and dilute hydrochloric acid; The solvent is at least one of ethanol and isopropanol; Heating for hydrolysis condensation means raising the temperature to 40-60°C for 4-8 hours; The amounts of the alkylsilane, mercaptosilane, catalyst and solvent are such that the molar ratio of the alkylsilane to the mercaptosilane is 1:0.4-0.
6. The amount of the catalyst is 1%-5% of the total mass of the alkylsilane and the mercaptosilane, and the amount of the solvent is 100%-300% of the total mass of the alkylsilane and the mercaptosilane.
6. The method for preparing a UV light-curing hydrophobic material for bathroom use according to claim 3, characterized in that: The catalyst is at least one of sulfuric acid and trifluoromethanesulfonic acid; The condensation reaction is carried out at 40 to 80° C. for 8 to 12 hours; The catalyst meets the following requirements: the amount of catalyst is D4, D4 C=C 1% to 5% of the total mass of the vinyl double head; The alkali is at least one of sodium carbonate and sodium bicarbonate.
7. A UV light-curing hydrophobic material for bathroom, characterized in that: The method for preparing the UV light-curing hydrophobic material for bathroom use according to any one of claims 1 to 6 is used for preparation.
8. The UV light-curing hydrophobic material for bathroom use according to claim 7, characterized in that: The UV light-curing hydrophobic material is mixed and a photoinitiator needs to be added for UV curing.
9. The UV light-curing hydrophobic material for bathroom use according to claim 7, characterized in that: The mixing of the UV light-curable hydrophobic material refers to adding organic zirconium nanoparticles, organic silicon resin and organic silicon material in a ratio of 1:1:1.7 to 2.
3.
10. The UV light-curing hydrophobic material for bathroom use according to claim 10, characterized in that: The photoinitiator refers to a compound that can generate free radicals under ultraviolet light irradiation, and is at least one of 2-hydroxy-2-methylpropiophenone, 1-hydroxy-cyclohexyl benzophenone, 2,4,6-trimethylbenzoyl-ethoxy-phenylphosphine oxide and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide; the added amount of the photoinitiator is 1% to 4% of the total mass of the organic zirconium nanoparticles, the organic silicon resin and the organic silicon material.
Citation Information
Patent Citations
Bathroom high polymer material
CN112430372A
Preparation method and application of nano zirconium-titanium composite sol / organosilicon modified hybrid resin
CN104725643A
Composition having siloxane polymer and particle
CN106612617A
Modified silicone coating composition
CN111373002A
External facing material for construction and coating liquid for building exterior
JP2011058273A